Pendampingan Penggunaan Aplikasi Balale Dalam Mendata Penerimaan Bantuan Bagi PPKS - Yuliana, Yuliana; Gudiato, Candra; Noviyanti, Noviyanti (Penerbit Widina, Widina Media Utama, 2025)
Technology plays an important role in improving the progress of a region that is located in a remote area and far from the center of economic growth. Through technology that has been developed and also as the fastest and widest media in presenting and accommodating information so that it is used in data and information storage. For the government and all Social Service, Women's Empowerment and Child Protection apparatus of Bengkayang Regency, technology is very much needed, Data storage and storage-based technology, so operators are also needed to manage the application in this case are service devices, Village Heads/Lurah, TKSK, and data collection officers who need assistance. The method used in the service is through stages such as Socialization by discussing with the head of the service and the head of the field in preparing activities, assistance and evaluation. This service aims to facilitate in managing and operating the application in recording Assistance Receipts for PPKS. The results of the assistance to the service devices, Village Heads/Lurah, TKSK, and data collection officers are directed to get to know the application features such as the PPKS data input form, get to know the Graph of data types based on villages and the number of PPKS recipients and explain the Manual Book which is a Learning Module in the use of the Balale Application.ABSTRAKTeknologi berperan penting dalam meningkatkan kemajuan suatu daerah yang lokasinya terpencil dan jauh dari pusat pertumbuhan ekonomi. Melalui Teknologi yang sudah dikembangkan dan juga sebagai media tercepat dan terluas dalam menyajikan dan menampung informasi sehingga digunakan dalam penampungan data dan informasi. Pengabdian ini bertujuan untuk mempermudah dalam mengelola dan mengoperasi aplikasi dalam mendata Penerimaan Bantuan Bagi PPKS. Metode yang digunakan meliputi Sosialisasi dan berdiskusi bersama kepala dinas dan kepala bidang dalam persiapan kegiatan, pendampingan dan evaluasi kepada petugas pendata PPKS (perangkat dinas, Kades/lurah, TKSK). Jumlah peserta pendampingan sekitar 40 peserta dan dilaksanakan di Aula Kantor Bupati. Hasil pezngabdian ini adalah pendampingan yang telah dilaksanakan kepada seluruh peserta; perangkat dinas, Kades/Lurah, TKSK, dan petugas pendata yaitu diarahkan untuk mengenal fitur aplikasi fitur seperti form input data PPKS, mengenal Grafik jenis data berdasarkan desa dan jumlah penerima PPKS dan menjelaskan Manual Book yang adalah Modul Pembelajaran dalam penggunaaan Aplikasi Balale.